Praktik Manajemen Sumber Daya Manusia dan Keterlibatan Pegawai: Efek Moderasi Peran Pengawasan - Lily Vianty; Ririn Handayani; Fahmi Oemar (CV. ITTC INDONESIA, 2025)
The study was conducted at the Riau Provincial Secretariat with the aim of examining the role of supervisors in moderating the influence of human resource management practices on employee engagement. The population of this study was 178 people. Based on this population size, in accordance with the Krejcie and Morgan (1970) table, the sample size for this study was 118 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a 1-5 point Likert scale. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that human resource management practices are positively related to employee engagement; the role of supervisors positively moderates the influence of management practices on employee engagement.